2016
DOI: 10.1089/sur.2015.205
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Site Infection after Laparoscopic Surgery for Colon Cancer

Abstract: To prevent SSI after laparoscopic surgery for colon cancer, triclosan-coated PDS Plus sutures should be used for abdominal closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…). After final review, data from 34 distinct studies were included in the final assessment, yielding a total of 38 data points (2 studies had multiple SSIs per surgical wound type). Surgical wound types in the included study list are shown in Table S2 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). After final review, data from 34 distinct studies were included in the final assessment, yielding a total of 38 data points (2 studies had multiple SSIs per surgical wound type). Surgical wound types in the included study list are shown in Table S2 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Rozzelle et al 47 Cerebrospinal fluid shunt surgery Yamashita et al 56 Colorectal surgery Nakamura et al 42 Colonic surgery…”
Section: Random-effects Modelmentioning
confidence: 99%
“…17 According to the various reported studies, significant differences were found in the SSI rates when different suture materials were used. 9,20 In the early 1970s, with the development of the synthetic absorbable polymer, polyglycolic acid, the new era of absorbable polymeric sutures was started which got extraordinary commercial success. 19 Now a day, absorbable sutures have become a treatment of choice over non-absorbable sutures.…”
Section: Discussionmentioning
confidence: 99%
“…Many papers have reported different preoperative, intraoperative, and postoperative risk factors for SSI in abdominal surgery [6][7][8], such as perioperative transfusion, cirrhosis, or anastomosis of the bowel. On the other hand, numerous studies have reported diabetic patients to be subject to postoperative infectious diseases including SSI [9][10][11]. Martin et al analyzed the association between diabetes and the risk of SSI in their large systematic review and meta-analysis and reported the overall effect size for the association between diabetes and SSI as odds ratio (OR) 1.53 [9].…”
Section: Introductionmentioning
confidence: 99%